2019
DOI: 10.3390/ijms20194798
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl Oxidase-Like 2 Protects against Progressive and Aging Related Knee Joint Osteoarthritis in Mice

Abstract: Background: The goal of this study was to determine if adenovirus-delivered LOXL2 protects against progressive knee osteoarthritis (OA), assess its specific mechanism of action; and determine if the overexpression of LOXL2 in transgenic mice can protect against the development of OA-related cartilage damage and joint disability. Methods: Four-month-old Cho/+ male and female mice were intraperitoneally injected with either Adv-RFP-LOXL2 or an empty vector twice a month for four months. The proteoglycan levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Further, studies have indicated the upregulation of LOXL2 in OA cartilage in response to injury, which may be considered as a naturally protective response that promotes anabolism while inhibiting specific catabolic response during OA pathophysiology (Alshenibr et al, 2017;Bais and Goldring, 2017). Likewise, a recent study further confirmed that systemic adenovirus-delivered LOXL2 expression or LOXL2 genetic overexpression both exhibited chondroprotective effects through inhibition of catabolic factors and IL-1β-induced NF-κB signaling in mice (Tashkandi et al, 2019). Also, Matrigel constructs of human chondrocytes from the knee joint and TMJ implanted in nude mice showed enhanced anabolic responses after LOXL2 transduction, including increased expression of sex determining region Y-box containing gene 9 (SOX9), aggrecan (ACAN), and COL2A1, whilst reduced the levels of extracellular matrix (ECM)-degrading enzymes matrix metalloproteinases and inhibited chondrocyte apoptosis (Alshenibr et al, 2017).…”
Section: Lysyl Oxidases In Cartilage Functioningmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, studies have indicated the upregulation of LOXL2 in OA cartilage in response to injury, which may be considered as a naturally protective response that promotes anabolism while inhibiting specific catabolic response during OA pathophysiology (Alshenibr et al, 2017;Bais and Goldring, 2017). Likewise, a recent study further confirmed that systemic adenovirus-delivered LOXL2 expression or LOXL2 genetic overexpression both exhibited chondroprotective effects through inhibition of catabolic factors and IL-1β-induced NF-κB signaling in mice (Tashkandi et al, 2019). Also, Matrigel constructs of human chondrocytes from the knee joint and TMJ implanted in nude mice showed enhanced anabolic responses after LOXL2 transduction, including increased expression of sex determining region Y-box containing gene 9 (SOX9), aggrecan (ACAN), and COL2A1, whilst reduced the levels of extracellular matrix (ECM)-degrading enzymes matrix metalloproteinases and inhibited chondrocyte apoptosis (Alshenibr et al, 2017).…”
Section: Lysyl Oxidases In Cartilage Functioningmentioning
confidence: 88%
“…The decreased expression of LOXs may attribute to reduction of HIF-1 activity in aging organisms (Rivard et al, 2000;Ceradini et al, 2004). Meanwhile, LOXL2 has recently been demonstrated as a potential chondroprotective factor in aging related joint osteoarthritis, mainly through inducing anabolic gene expression and attenuating catabolic genes (Bais and Goldring, 2017;Tashkandi et al, 2019). Thus, restoration of collagen and elastic fiber synthesis in juvenile ECM components though regulation of signaling pathways governing LOX expression may become a promising therapeutic approach for amelioration of aging-associated cartilage degeneration and enhanced cartilage regeneration.…”
Section: Potential Links Between Lox and Aging-associated Cartilage Dmentioning
confidence: 99%
“…As described in our earlier studies 19 , 20 , adenoviruses for LOXL2 expression co-expressing Red Fluorescent Protein (RFP) was used for verification of virus transduction and efficient of delivery Ad-CMV-RFP-CMV-hLOXL2-His; referred to as Ad-RFP-LOXL2), and the empty vector control (Ad-RFP-Empty) were custom synthesized (ADV-214438) by Vector Biolabs, PA. These adenovirus particles were amplified in 293 T cells and quantified using an adenovirus quantification kit (Cell Biolabs).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted by the Trizol protocol according to the manufacturer’s instructions (Qiagen) as described earlier 19 , 20 . RT-qPCR analysis was performed using TaqMan gene expression assays from Life Technologies, according to a standard protocol 33 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation